The LRR-RLK Protein HSL3 Regulates Stomatal Closure and the Drought Stress Response by Modulating Hydrogen Peroxide Homeostasis - Liu, Xuan-shan; Liang, Chao-chao; Hou, Shu-guo; Wang, Xin; Chen, Dong-hua; Shen, Jian-lin; Zhang, Wei; Wang, Mei (Frontiers in Plant Science, 2020)
Guard cells shrink in response to drought stress and abscisic acid (ABA) signaling, thereby reducing stomatal aperture. Hydrogen peroxide (H2O2) is an important signaling molecule acting to induce stomatal closure. As yet, the molecular basis of control over the level of H2O2 in the guard cells remains largely unknown. Here, the LRR-RLK protein HSL3 has been shown to have the ability to negatively regulate stomatal closure by modulating the level of H2O2 in the guard cells. HSL3 was markedly up-regulated by treating plants with either ABA or H2O2, as well as by dehydration. In the loss-of-function hsl3 mutant, both stomatal closure and the activation of anion currents proved to be hypersensitive to ABA treatment, and the mutant was more tolerant than the wild type to moisture deficit; the over-expression of HSL3 had the opposite effect. In the hsl3 mutant, the transcription of NADPH oxidase RbohF gene involved in H2O2 production showed marked up-regulation, as well as the level of catalase activity was weakly inducible by ABA, allowing H2O2 to accumulate in the guard cells. HSL3 was concluded to participate in the regulation of the response to moisture deficit through ABA-induced stomatal closure triggered by the accumulation of H2O2 in the guard cells.